THE MEDIATING ROLE OF MOTIVATION BETWEEN REMUNERATION AND PERFORMANCE - Dei, Abdul Rajab; Manan, Abdul; Respati, Harianto (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This research aims to examine the remuneration effect on performance using motivation as the mediating variable. Design/methodology/approach- The population of the research is all educational staff who work in one of public education institutions in Malang which have been applied remuneration system. Sample selection was conducted through a stratified random sampling technique. This study used a structured questionnaire to collect data and Pearson correlation and regression models were used to analyze data. Findings- The results showed that remuneration had a significant effect on motivation and employee performance, and there was a significant effect of motivation in mediating the remuneration effect on employee performance. This study recommends the need for more attention to motivation because of its essential role in improving employee performance Implication- The significant motivation role in improving employee performance is expected to be a concern for leaders to encourage employees in carrying out and completing their work rather than merely focused on remuneration itself. The goal is not only for individual purposes but also for the benefit of the organization. Limitation- This research uses a case study approach so that it only takes the perception of the remuneration implementation which occurs in one place. Future research should be able to expand sampling in order to generalize the results.